Two- versus three-alternative concurrent-chain schedules: a test of three models. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2000)
Two experiments with pigeons used concurrent-chain procedures with variable-interval schedules as initial links and different delays to food as terminal links. Two schedules were present in all sessions. but a 3rd schedule was alternately present and absent in successive sessions. When the 3rd schedule delivered food with no terminal-link delay, the presence of this schedule led to an increase in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. When the terminal-link delay for the 3rd schedule was 30 s, the presence of this schedule led to a decrease in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. These results are inconsistent with the predictions of R. Grace's (1994) contextual-choice model, but they are consistent with 2 other mathematical models-delay-reduction theory and the hyperbolic value-added model.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-282-629-182-734 tex.type: [object Object]
Keywords: *Choice Behavior; *Columbidae; *Conditioning; Operant; Analysis of Variance; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Models; Psychological; analysis of variance; animal; article; decision making; dept.psy; instrumental conditioning; pigeons and doves; psychological model